Simulation and optimization of bio-chemical microreactors - Rannacher, Rolf; Schmich, Michael (Mathematics – key technology for the future, 2008)
We describe the main steps in the development of a tool for the numerical simulation and optimization of a bio-chemical microreactor. Our approach comprises a 2D/3D grid generator for the prototypical Lilliput R chip, a stabilized finite element discretization in space coupled with an implicit time-stepping scheme and level-set techniques.